2020
DOI: 10.1097/md.0000000000019938
|View full text |Cite
|
Sign up to set email alerts
|

Brain-derived neurotrophic factor and glutathione peroxidase as state biomarkers in alcohol use disorder patients undergoing detoxification

Abstract: The pathophysiology of alcohol use disorder (AUD) is not totally clear. The aim of this study was to investigate the serum levels of brain-derived neurotrophic factor (BDNF) and oxidative stress markers in AUD patients during alcohol detoxification. Evaluation of changes in BDNF, glutathione peroxidase (GPX), catalase, superoxide dismutase, thiobarbituric acid reactive substances, 8-hydroxy 2’-deoxyguanosine, PCC and S100B were carried out. 14 AUD inpatients and 20 healthy control subjects were recr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 51 publications
(75 reference statements)
2
12
0
Order By: Relevance
“…This may be explained by a compensatory mechanism to eliminate possible O 2 - excess. Previous studies had similar results ( 8 ), with decreased concentrations in ethanol users ( 10 , 11 , 24 ) and with no difference between groups ( 27 , 29 ).…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…This may be explained by a compensatory mechanism to eliminate possible O 2 - excess. Previous studies had similar results ( 8 ), with decreased concentrations in ethanol users ( 10 , 11 , 24 ) and with no difference between groups ( 27 , 29 ).…”
Section: Discussionsupporting
confidence: 61%
“…Studies that used the TBARS method to determinate MDA activity also reported higher levels in ethanol users ( 9 - 12 , 23 , 24 ). Other studies also reported increased MDA activity, but the difference was not significant ( 25 - 27 ). When MDA was evaluated in red blood cells, again higher results were found in ethanol users ( 21 ).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…The pathophysiology of AUD is not clear. BDNF might be related to neuronal plasticity and the reward system [ 61 ]. A study investigating BDNF serum and oxidative stress markers in AUD during alcohol detoxification reported that oxidative stress markers serum levels were significantly higher in the AUD patients, while BDNF levels were lower.…”
Section: Resultsmentioning
confidence: 99%
“…After alcohol detoxification treatment, the GPX levels in the AUD group dropped, and the BDNF levels rose. The authors suggested that serum BDNF and GPX levels might be state biomarkers for AUD patients undergoing alcohol detoxification [ 61 ].…”
Section: Resultsmentioning
confidence: 99%